Report of a clinical case of a myocardial infarction with non- obstructive coronary arteries in a young male patient (La U Investiga, 2023)
We describe a case of a male patient with MINOCA, due to an isolated left ventricular myocardial infarction with microvascular obstruction identified on cardiac MRI. The importance in its recognition and search for the etiology lies in the long-term prognosis, given the higher incidence of major cardiovascular events. This case highlights that even a comprehensive, guideline-based evaluation of these patients may initially fail to detect the underlying pathology.